Extreme climate impacts over benthic assemblages and carbon dynamics on tropical mangrove ecosystems : extreme climate impacts on the dynamics of a tropical mangrove ecosystems - Gomes, Luiz Eduardo de Oliveira (2022)
The period 2014-2016 was extremely dry in Southeast Brazil, being the historical record, since 1950, for many areas in the region. In parallel, in June 2016, 500 hectares of mangroves in the Piraquê Açú-Mirím estuary were impacted by a hailstorm with wind gusts of more than 100 km/h. Such impact is a snapshot of the climate changes events that are impairing the world. In this sense, this thesis evaluated the effects of climate change on the dynamics of tropical mangroves; highlighting the impacts of extreme climate events on mangrove ecosystem and their functions. The first chapter highlights the reduction of litterfall production of the mangrove forest impacted by the extreme climate events to less than 1/3 compared to unimpacted mangroves. The second chapter evidence the mangrove ecosystem carbon loss related to the damages to forest structure associated to the erosion and/or degradation of soil first meter. In addition, by compiling other studies, this chapter updated the mangrove carbon stock potential to 0.52 Petagram of carbon along their 940,000 hectares distributed along the Brazilian coast, over 2-folds of previously estimated. The third chapter proposes an support carbon service to the traditional carbon stock already considered in nature-based solutions such as ecosystems conservation and restoration. By this, we estimated the annual gain of organic carbon on the soil surface by Brazilian mangroves and compared among pristine mangroves, under effluent pollution, deforested, impacted by drought or flood extreme events. The analyses evidence the potential of the applied proposal to climate mitigation in local-regional scales. Finally, the monitoring of the impacted regions are recommended to assess the effects of climate events on biodiversity and carbon stocks degradation, as well as the development of more efficient mitigation actions